Research as the basis for decision-making in reindeer husbandry - Norvik, Erling (Rangifer, 1990)
The principal challenge for Norwegian reindeer husbandry in Finnmark today - seen from the viewpoint of both the central political authorities and the industry itself - is disequilibrium between the number of reindeer and their forage resources. Productivity is low, the economy is worse and a large number of reindeer owners have an unsatisfactory number of animals and an unsatisfactory income. The animals are becoming smaller and smaller. Social and economic problems are increasing. There is an obvious danger of long term damage to the pasture areas. How long term, nobody knows. There are no clear research results to guide us but, I am glad to say, research is under way and satellite imagery represents a good, new tool. Research must have a free hand - but it cannot be fully independent. Researchers must try to direct their activities towards providing both the industry and the politicians with a solid basis on which to base their decisions. It is therefore my hope that «productive» research receives as high priority as possible. With limited funding available for research and the relatively small size of the indus-try, it is important that its requirements and its own demands for help from researchers be attended to.